An anodic aromatic C, C cross-coupling reaction using parallel laminar flow mode in a flow microreactor1. Issue 23 (21st March 2015) - Arai, Toshihiro; Tateno, Hiroyuki; Nakabayashi, Koji; Kashiwagi, Tsuneo; Atobe, Mahito
<x xml:space="preserve">Abstract</x> An efficient anodic aromatic C, C cross-coupling reaction was successfully demonstrated by using parallel laminar flow mode in a two-inlet flow microreactor.